Effect of The Composition of Lindur Fruit (Bruguiera gymnorrhiza) starch Flour and Chitosan on Characteristics of Biodegradable Plastics - Agustin, Dhita Widya Dyah; Dewi, Eko Nurcahya; Rianingsih, Laras (Politeknik Ahli Usaha Perikanan, 2023)
Lindur fruit starch flour has a high starch content, so it can be used as a biodegradable plastic manufacturing material. The manufacture of biodegradable plastic made from starch alone will produce plastic with low tensile strength and less flexible, so it is necessary to add the chitosan to improve the characteristics. The purpose of this study is to determine the effect and best composition of the lindur fruit starch flour-chitosan. The manufacture of biodegradable plastic begins by mixing a solution of lindur fruit starch flour with a solution of chitosan and glycerol. The solution is heated using a temperature of 70-80oC, then printed on a glass plate. The research design used was a Complete Randomized Design with the composition of lindur fruit starch flour-chitosan 10:0, 9:1, 8:2, 7:3, and 6:4. The results showed that the best tensile strength values was the treatment of lindur fruit starch flour-chitosan 7:3 and 6:4 which is 20.23 MPa and 20.61 MPa. The best elongation value was the treatment of lindur fruit starch flour-chitosan 9:1 which is 6.71%. The best biodegradability test was the treatment of lindur fruit starch flour-chitosan 10:0 which is 15.93 mg/day. The best water resistance and antibacterial tests were in the treatment of lindur fruit starch flour-chitosan 6:4) which is 86.5% and the inhibition zone was 2 mm for Escherichia coli bacteria and 1.4 mm for Staphylococcus aureus bacteria.